Metabolic Responses of Subtropical Microplankton After a Simulated Deep-Water Upwelling Event Suggest a Possible Dominance of Mixotrophy Under Increasing CO2 Levels - Tames Espinosa, Maria Teresa; Martínez Sánchez, Ico; Romero Kutzner, Vanesa; Coca Saenz De Albéniz, Josep; Algueró-Muñiz, María; Horn, Henriette G.; Ludwig, Andrea; Taucher, Jan; Bach, Lennart; Riebesell, Ulf; Packard, Theodore Train; Gómez Cabrera, María Milagrosa (Frontiers in Marine Science, 2020)
In the autumn of 2014, nine large mesocosms were deployed in the oligotrophic subtropical North-Atlantic coastal waters off Gran Canaria (Spain). Their deployment was designed to address the acidification effects of CO2 levels from 400 to 1,400 μatm, on a plankton community experiencing upwelling of nutrient-rich deep water. Among other parameters, chlorophyll a (chl-a), potential respiration (Φ), and biomass in terms of particulate protein (B) were measured in the microplankton community (0.7–50.0 μm) during an oligotrophic phase (Phase I), a phytoplankton-bloom phase (Phase II), and a post-bloom phase (Phase III). Here, we explore the use of the Φ/chl-a ratio in monitoring shifts in the microplankton community composition and its metabolism. Φ/chl-a values below 2.5 μL O2 h−1 (μg chl-a)−1 indicated a community dominated by photoautotrophs. When Φ/chl-a ranged higher, between 2.5 and 7.0 μL O2 h−1 (μg chl-a)−1, it indicated a mixed community of phytoplankton, microzooplankton and heterotrophic prokaryotes. When Φ/chl-a rose above 7.0 μL O2 h−1 (μg chl-a)−1, it indicated a community where microzooplankton proliferated (>10.0 μL O2 h−1 (μg chl-a)−1), because heterotrophic dinoflagellates bloomed. The first derivative of B, as a function of time (dB/dt), indicates the rate of protein build-up when positive and the rate of protein loss, when negative. It revealed that the maximum increase in particulate protein (biomass) occurred between 1 and 2 days before the chl-a peak. A day after this peak, the trough revealed the maximum net biomass loss. This analysis did not detect significant changes in particulate protein, neither in Phase I nor in Phase III. Integral analysis of Φ, chl-a and B, over the duration of each phase, for each mesocosm, reflected a positive relationship between Φ and pCO2 during Phase II [α = 230·10−5 μL O2 h−1 L−1 (μatm CO2)−1 (phase-day)−1, R2 = 0.30] and between chl-a and pCO2 during Phase III [α = 100·10−5 μg chl-a L−1 (μ atmCO2)−1 (phase-day)−1, R2 = 0.84]. At the end of Phase II, a ...